Bahasa Ende dan Pengaruhnya terhadap Perkembangan Globalisasi - Saud, Jefriyanto Saud; Paris, Atika Salman (Program Studi Magister Linguistik Terapan UNJ, 2024)
This study investigates the use and preservation of the Ende language in Ende Regency, East Nusa Tenggara. The methodology employed includes qualitative analysis of data collected through observations, interviews, and literature reviews. The findings indicate that although the Ende language has many speakers, its usage has significantly declined, particularly among the younger generation who prefer to use Indonesian or foreign languages. The Ende language is still used in daily communication by only 40% of children and 30% of teenagers. Migration, media influence, and a lack of community awareness regarding the importance of regional languages are all factors contributing to this decline. The study concludes that the government, educational institutions, and the community must collaborate to preserve the Ende language. This research fills a gap in previous studies on the preservation of local languages and provides practical implications for educational and cultural policies.